Analisis Yuridis Tindakan Penyalahgunaan Izin Keimigrasian oleh Tenaga Kerja Asing di Kota Batam - Lu Sudirman23; Eva Dian Sari (Fakultas Hukum, Universitas Internasional Batam, 2018)
With the increasing foreign investment in Batam City is also a consequence of the increase in the number of foreign workers who enter the Batam City. In recent years, the situation of illegal foreign workers in Indonesia has increased. Therefore, the authors doing research about Juridical Analysis Against the Misuse of Immigration Permits by Foreign Workers in Batam City with great hope to expand knowledge and be used as guidelines for society or government. The final project of this thesis aims to know the provisions and requirements that must be fulfilled by employers and foreign workers who will be employed within the territory of the Republic of Indonesia, to know the consequences and legal consequences for foreign workers who misuse immigration permits in Batam City, and to analyze factors and the impacts arising from the misuse of immigration permits by foreign workers in Batam City. The research method used by the authors in the preparation of this research is the empirical normative is to conduct literature research on the applicable Legislation and analyze the supporting data from relevant agencies on the issues discussed in this study. Based on the results of research conducted by the authors can be concluded that against foreign workers who misuse immigration permits in Batam City will be deported and deterrenced with a period of no more than 6 (six) months and the removal of IMTA for employers who employ illegal foreign workers. As for several factors that cause the increasingly illegal foreign workers in Batam City such as the implementation of policies that have the potential to bring out illegal foreign workers; supervision conducted not yet maximal; as well as non-compliance of employers to the prevailing regulations that will result in the impact of increasing unemployment, the increasing crime and increasing misuse of drugs in Batam City.